Genetic landscape of a large cohort of Primary Ovarian Insufficiency: New genes and pathways and implications for personalized medicine - Heddar, Abdelkader; Ogur, Cagri; Da Costa, Sabrina; Braham, Ines; Billaud-Rist, Line; Findikli, Necati; Beneteau, Claire; Reynaud, Rachel; Mahmoud, Khaled; Legrand, Stephanie; Marchand, Maud; Cedrin-Durnerin, Isabelle; et al. (ELSEVIER, 2022)
Background Primary Ovarian Insufficiency (POI), a public health problem, affects 1-3.7% of women under 40 yield-ing infertility and a shorter lifespan. Most causes are unknown. Recently, genetic causes were identified, mostly in single families. We studied an unprecedented large cohort of POI to unravel its molecular pathophysiology.Methods 375 patients with 70 families were studied using targeted (88 genes) or whole exome sequencing with pathogenic/likely-pathogenic variant selection. Mitomycin-induced chromosome breakages were studied in patients' lymphocytes if necessary. Findings A high-yield of 29.3% supports a clinical genetic diagnosis of POI. In addition, we found strong evidence of pathogenicity for nine genes not previously related to a Mendelian phenotype or POI: ELAVL2, NLRP11, CENPE, SPATA33, CCDC150, CCDC185, including DNA repair genes: C17orf53(HROB), HELQ, SWI5 yielding high chromo-somal fragility. We confirmed the causal role of BRCA2, FANCM, BNC1, ERCC6, MSH4, BMPR1A, BMPR1B, BMPR2, ESR2, CAV1, SPIDR, RCBTB1 and ATG7 previously reported in isolated patients/families. In 8.5% of cases, POI is the only symptom of a multi-organ genetic disease. New pathways were identified: NF-kB, post-translational regulation, and mitophagy (mitochondrial autophagy), providing future therapeutic targets. Three new genes have been shown to affect the age of natural menopause supporting a genetic link.Interpretation We have developed high-performance genetic diagnostic of POI, dissecting the molecular pathogene-sis of POI and enabling personalized medicine to i) prevent/cure comorbidities for tumour/cancer susceptibility genes that could affect life-expectancy (37.4% of cases), or for genetically-revealed syndromic POI (8.5% of cases), ii) predict residual ovarian reserve (60.5% of cases). Genetic diagnosis could help to identify patients who may benefit from the promising in vitro activation-IVA technique in the near future, greatly improving its success in treating infertility.Funding Universite? Paris Saclay, Agence Nationale de Biome?decine.Copyright (c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)
Keywords: Primary ovarian insufficiency; Personalized medicine; NF-KB; Post-translational regulation; Meiosis; DNA repair genes; Mitophagy; PULMONARY ARTERIAL-HYPERTENSION; OF-FUNCTION MUTATIONS; VARIANTS; IDENTIFICATION; ASSOCIATION; FERTILITY; CARRIERS; BMPR2; WOMEN; General & Internal Medicine; Research & Experimental Medicine